To begin solving for X, we need it to be an equation rather than an expression. This I what I mean:
(-6x+51) = ?
We need to figure out what comes after the equal sign in order to solve for X.
The angle measures inside a triangle always add up to 180°. We are given that Angle P = 80° and Angle Q = 43°. With this given information it makes it simple to figure out the missing angle measure inside the triangle:
80+43= 123
180-123= 57
So the unknown angle measure in that triangle is 57°. Now we will subtract 57° from 180°. Why? Because a straight line is 180° and that's exactly the angle measure of the side that Angle R and Angle Q are on (hope that isn't to confusing )
With that being said, (-6x+51)° plus 57° would equal 180°. We don't need the 57 in the equation to solve for X though, because now we now that (-6x+57)= 123. That's because 180-57= 123, so we now know the outside angle measure next to Angle R equals 123°.
We can finally solve for X:
-6x+51= 123
(subtract 51 from both sides to even out the equation. We subtract because that's the inverse operation of addition)
-6x=72
(now we simply divide -6 on both sides, because division is the inverse operation of multiplication)
x= -12
(Hope this helps and wasn't to confusing for you to understand :). Let me know if you have any other questions about this problem.)